2008
DOI: 10.1590/s0104-56872008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de idosos em um teste de fala na presença de ruído

Abstract: the presence of the noise during the production of speech sounds is disadvantageous for elders, independently of the presence of hearing loss, but having a higher impact for those with hearing loss problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
0
10
0
9
Order By: Relevance
“…Presbycusis, which is the hearing loss that comes with aging, can take place throughout the entire auditory system, from the middle ear to the auditory pathways, including the cortex, and it can occur in single or multiple locations, resulting in decreased auditory sensitivity and reduced speech comprehension at suprathreshold levels* (10) . Difficulties and decreased ability to hear in adverse situations have also been observed, such as speech reception in the midst of noise by elderly people without peripheral hearing loss (11) . In one study, elderly people were given a questionnaire about possible hearing problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presbycusis, which is the hearing loss that comes with aging, can take place throughout the entire auditory system, from the middle ear to the auditory pathways, including the cortex, and it can occur in single or multiple locations, resulting in decreased auditory sensitivity and reduced speech comprehension at suprathreshold levels* (10) . Difficulties and decreased ability to hear in adverse situations have also been observed, such as speech reception in the midst of noise by elderly people without peripheral hearing loss (11) . In one study, elderly people were given a questionnaire about possible hearing problems.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, elderly people were given a questionnaire about possible hearing problems. It was found that 15.4% of those without hearing loss reported difficulty hearing in certain situations (11) .…”
Section: Introductionmentioning
confidence: 99%
“…The fact that tonal hearing thresholds were within the normal range is not sufficient to ensure adequate recognition of speech in situations where there is competitive noise 28 . Authors 27 indicate that the aging of the auditory system can interfere in speech recognition, even when peripheral hearing is normal.…”
Section: Resultsmentioning
confidence: 99%
“…The brain requires some time to use the new acoustic information generated by the auditory prosthesis 3-7. The main complaint by those with hearing loss refers to the difficulty in oral communication, and this complaint is persistent in new auditory prosthesis users who, even after amplification, find difficulty in recognizing sounds. Thus, acclimatization becomes the phonoaudiologist's and patient's great ally in the process of adaptation to auditory prostheses 8. Auditory processing refers to the process involved in the detection and interpretation of sound events 9,10 . It involves the detection of acoustic events, capacity of discrimination with regard to location, spectrum, amplitude, time and ability to group components of the acoustic signal in figure--ground relationships.…”
Section: Methodsmentioning
confidence: 99%